Fostering Student Engagement and Success in STEM Education: An AI-Driven Exploration of High Impact Practices from Cross-Disciplinary General Education Courses - Ramasamy, Vijayalakshmi; Singsen, Doug; Walia, Gursimran S. (Journal of Engineering Education Transformations, 2025)
Due to the increase in data and software tools, the need for programmers and data analysts has risen in the United States during the 21st century. As a result, more students are enrolling in Computer Science, Information Technology, and Data Science programs nationwide. However, switching to online and blended learning and using cyberlearning tools have presented new challenges for student learning, retention, and program success. One way to overcome these challenges and improve student achievement is to implement evidence-based pedagogical strategies and innovative technologies within clear theoretical frameworks. Recent studies have shown that various Learning Engagement Strategies (LESs) in STEM education, such as gamification, active learning, feedback and assessment, and interactive multimedia, significantly increase student engagement and course completion rates. High-Impact Practices (HIPs), identified as crucial by Kuh in 2008, have become powerful tools for enhancing student involvement, retention, and completion in higher education. This article explores practices that can enhance student learning and success that have many benefits, including more robust relationships between students and faculty, cooperative learning, quick feedback, inclusive environments, and conflict resolution. The study uses NLP-based text analytics to investigate the application and impact of these High-Impact Practices (HIPs) across different disciplines. Firstly, it identifies the most prevalent HIPs in various General Education (Gen Ed) disciplines that impact student success. Secondly, it formulates AIdriven recommendations for cultivating a student-centric learning environment through HIPs within STEM education. The results of empirical analyses using course materials, survey data, syllabi, and pre/post-workshop surveys sourced from around 65 Gen Ed course at a small public university provides valuable insights into successful HIPs for STEM courses that can help instructors improve their online and blended course designs. By implementing these practices, educators can increase student engagement, retention, and completion rates across diverse student populations in Gen Ed STEM courses.